Brain Injury and Neurodegeneration: Molecular, Functional, and Translational Approach - Meenakshi Ahluwalia; Pankaj Gaur; Kumar Vaibhav (Biomedicines, 2023)
Recently, we have achieved substantial progress in our understanding of brain injury and neurodegeneration [...]